2006
DOI: 10.1103/physrevb.73.033318
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Curie temperature in ferromagnetic/ferroelectric hybrid double quantum wells

Abstract: We propose a ferromagnetic/ferroelectric hybrid double quantum well structure, and present an investigation of the Curie temperature (T c ) modulation in this quantum structure. The combined effects of applied electric fields and spontaneous electric polarization are considered for a system that consists of a Mn δ-doped well, a barrier, and a p-type ferroelectric well. We calculate the change in the envelope functions of carriers at the lowest energy subband, resulting from applied electric fields and switchin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There have been many studies on the control of the spin states in double quantum wells or double quantum dots by using bias voltage [1][2][3]. In our former study, we have demonstrated electric-field-controlled ferromagnetism in Mn δ-doped asymmetric conventional double quantum wells [2] and in hybrid double quantum wells [4]. However, in the previous work, our primary interest was the control of the ferromagnetic transition temperature by either applying electric field or reversing dipole polarization.…”
mentioning
confidence: 92%
“…There have been many studies on the control of the spin states in double quantum wells or double quantum dots by using bias voltage [1][2][3]. In our former study, we have demonstrated electric-field-controlled ferromagnetism in Mn δ-doped asymmetric conventional double quantum wells [2] and in hybrid double quantum wells [4]. However, in the previous work, our primary interest was the control of the ferromagnetic transition temperature by either applying electric field or reversing dipole polarization.…”
mentioning
confidence: 92%